2021
DOI: 10.1155/2021/9923816
|View full text |Cite
|
Sign up to set email alerts
|

Efflux Pump Activity and Mutations Driving Multidrug Resistance in Acinetobacter baumannii at a Tertiary Hospital in Pretoria, South Africa

Abstract: Acinetobacter baumannii (A. baumannii) has developed several resistance mechanisms. The bacteria have been reported as origin of multiple outbreaks. This study aims to investigate the use of efflux pumps and quinolone resistance-associated genotypic mutations as mechanisms of resistance in A. baumannii isolates at a tertiary hospital. A total number of 103 A. baumannii isolates were investigated after identification and antimicrobial susceptibility testing by VITEK2 followed by PCR amplification of blaOXA-51. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 69 publications
1
6
0
Order By: Relevance
“…In the present study, 10 studies showed that overexpression of an efflux system can be an efficient mechanism for drug resistance in A. baumannii isolates[ 50 56 57 58 59 60 61 62 63 78 ] The corresponding structural efflux pump genes are part of plasmids, transposons, or resistance islands,[ 86 ] which MDR A. baumannii acquires in hospital units such as intensive care units (ICU) and burns units or from the environment. Efflux pumps with other antibiotic resistance mechanisms allow bacteria to reach high-level resistance; moreover, they weakly increase the MICs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present study, 10 studies showed that overexpression of an efflux system can be an efficient mechanism for drug resistance in A. baumannii isolates[ 50 56 57 58 59 60 61 62 63 78 ] The corresponding structural efflux pump genes are part of plasmids, transposons, or resistance islands,[ 86 ] which MDR A. baumannii acquires in hospital units such as intensive care units (ICU) and burns units or from the environment. Efflux pumps with other antibiotic resistance mechanisms allow bacteria to reach high-level resistance; moreover, they weakly increase the MICs.…”
Section: Discussionmentioning
confidence: 99%
“…[ 89 ] Beheshti et al ., and other studies reported resistance to the mentioned antibiotics and detected adeA, adeB, adeC, adeJ , and abeM genes. [ 56 57 58 59 60 62 78 ] AdeIJK is the second RND efflux system, which contributes to intrinsic resistance to b-lactams. [ 63 ]…”
Section: Discussionmentioning
confidence: 99%
“…In Acinetobacter baumannii, the most common mechanism of resistance is fluoroquinolone resistance, which is acquired by spontaneous mutations in the gyrA, gyrB and parC genes which encode gyrase and topoisomerase IV (88). The existence of the efflux pump adeABC is still an important cause of drug resistance in Acinetobacter baumannii (89).…”
Section: Mechanisms Of Drug Resistance and Their Clinical Implicationsmentioning
confidence: 99%
“…Nogbou et al. found that A. baumannii with mutations in both the parC and gyrA genes had higher levels of resistance to tigecycline than strains without mutations ( Nogbou et al., 2021 ). Hammerstrom et al.…”
Section: Resistance Mechanismsmentioning
confidence: 99%